PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN PASIEN TENTANG PENCEGAHAN INFEKSI MENULAR SEKSUAL DI WILAYAH KERJA UPTD PUSKESMAS JEKAN RAYA PALANGKA RAYA - Suryagustina, Suryagustina,; Siti Santy Sianipar,; Lodia Kristin Manipada (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2017)
Sexually transmitted infections has now become an International problem and in a relatively rapid periods there has been an increase in the number of sufferers in the various of countries. Sexually transmitted infection are diseases arising from transmitted through sexual intercourse. Based on the preliminary results of the survey in the region are almost never receive health education about sexually transmitted infections even though the area is adjacent to the localization. This study aims to determine the effect of Health Education on the Level of Patients Knowledge about the Prevention of Sexually Transmitted Infections in the Working Area at Jekan Raya Health Center. The design of this study is pre-experiment approach one-group pre-post test design. The sampling technique used is accidental sampling, with sample are 30 respondents and analyzed with the Wilcoxon statistical test. The results of analysis by using the Wilcoxon test obtained p-value 0.000 < 0.05, which means Ha accepted that there is an influence of health education on the level of patients' knowledge about the prevention of sexually transmitted infections. It is expected that the results of this study can be used as a source of information for research and improving health care by providing health education not only to those who are at risk but to the general population. Because they also need to know about sexually transmitted infections and their prevention.